Molecular detection of Salmonella enterica serovar Typhi by Vi-qPCR - Mohamed Shakrin N.N.S.; Abdul Wahab A.H.; Ramasamy R.P.; Wan Yussof W.N.; Noordin N.; Verashahib K.; Jahis R.; Siti Noor Adnalizawati Adnan (Universiti Sains Malaysia, 2024)
Aims: To develop a real-time polymerase chain reaction system Vi-qPCR in the detection of Salmonella enterica serovar Typhi (S. Typhi), targeting the vexC gene encoding for Vi antigen (capsular polysaccharide antigen) and to evaluate its sensitivity and specificity performance using pure cultures of S. Typhi and other enteric pathogens. Methodology and results: Microbiological, biochemical and serotyping tests were conducted to determine the phenotypic characteristics of S. Typhi and other enteric pathogens in our collection. Primers were designed using Primer3 software and their in-silico specificity were analysed using Basic Local Alignment System Tool (BLAST). Optimisation of PCR annealing temperature was done prior to assessment of sensitivity and specificity performance against artificial serially diluted seeded stools. The primers were found to be 100% specific in the detection of S. Typhi towards 32 tested clinical strains. Verification of gene amplification by comparing the nucleotide sequences against reference genes in the GenBank database revealed high specificity to S. Typhi. Statistical analysis indicates that this method results in 100% sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Moreover, Vi-qPCR allows the detection of S. Typhi as low as 131.4 CFU/g of stool sample. Conclusion, significance and impact of study: A rapid and sensitive method for detection of Salmonella enterica serovar Typhi (S. Typhi) is desired as a diagnostic tool to improve typhoid management. The Vi-qPCR represent a promising non-invasive diagnostic tool for medical microbiology laboratories as a method for the detection of S. Typhi in both pure culture and stool specimens especially in chronic asymptomatic carriers where shedding of S. Typhi is intermittent and sometimes occurs in low level. 2018 Universiti Sains Malaysia.